الرقية الشرعية مفاهيم وضوابط - احتيوش وائل موسى سليمان (Sharwes Scientific Journal, 2024)
Satan has many forms of harming humans, including touch, magic, and the evil eye. Therefore, Islamic law approved treatment with ruqyah, and made it a beneficial reason for healing with His permission - Glory be to Him - and many people have resorted to it seeking treatment, and some who do not understand its rulings have also dabbled in it, and it has been marred by many violations. And legal transgressions, and therefore the need to know the legal provisions for ruqyah and what is related to it has increased.